Genomic Alterations in Head and Neck Squamous Cell Carcinoma: Level of Evidence According to ESMO Scale for Clinical Actionability of Molecular Targets (ESCAT). (2021) - Marret, Grégoire; Bièche, Ivan; Dupain, Célia; Borcoman, Edith; du Rusquec, Pauline; Ricci, Francesco; Hescot, Ségolène; Sablin, Marie-Paule; Tresca, Patricia; Bello, Diana; Dubot, Coraline; Loirat, Delphine; et al.
Abstract : Development of high-throughput technologies helped to decipher tumor genomic landscapes revealing actionable molecular alterations. We aimed to rank the level of evidence of recurrent actionable molecular alterations in head and neck squamous cell carcinoma (HNSCC) on the basis of the European Society for Medical Oncology (ESMO) Scale for Clinical Actionability of Molecular Targets (ESCAT) to help the clinicians prioritize treatment. We identified actionable alterations in 33 genes. HRAS -activating mutations were ranked in tier IB because of the efficacy of tipifarnib (farnesyltransferase inhibitor) in HRAS -mutated patients with HNSCC (nonrandomized clinical trial). Microsatellite instability (MSI), high tumor mutational burden (TMB), and NTRK fusions were ranked in tier IC because of PD-1 and TRK tyrosine kinase inhibitors tissue-agnostic approvals. CDKN2A -inactivating alterations and EGFR amplification were ranked in tier IIA because of the efficacy of palbociclib (CDK4/6 inhibitor) and afatinib (tyrosine kinase inhibitor) in these respective molecular subgroups in retrospective analyses of clinical trials. Molecular alterations in several genes, including PIK3CA gene, were ranked in tier IIIA because of clinical benefit in other tumor types, whereas molecular alterations in IGF1R and TP53 genes were ranked in tier IVA and tier V, respectively. The most compelling actionable molecular alterations in HNSCC according to ESCAT include HRAS -activating mutations, MSI, high TMB, NTRK fusions, CDKN2A -inactivating alterations, and EGFR amplification.